Bimbingan Perkawinan Mubadalah Untuk Mencegah Perceraian di Kota Pekalongan - Nadhifatuz Zulfa; Khaerunnisa Tri Darmaningrum; Raji Hermawan; Dewi Rosida (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Divorce in the city of Pekalongan is becoming a trend. The divorce rate is always increasing, even during the covid-19 pandemic and post pandemic. This paper intends to develop an appropriate formulation of mublah marriage guidance to prevent divorce in the city of Pekalongan, by emphasizing the understanding of the mubadalah concept through 5 pillars of marriage: (a) commitment to a strong bond of promise as a mandate from Allah (mitsaq ghalizh), (b) the principle of in pairs and mutually (zawaj), (c) mutual comfort behavior (taradh), (d) treat each other well (muasyaroh bil ma'ruf), (e) the habit of mutual discussion together (deliberation). The purpose of this study was to obtain the right formulation of mubadalah marriage guidance to prevent divorce. This study uses the Research and Development method, with three tests, (1) expert judgement (rational test), with valid results (model can be used), (2) limited scale trial (empirical test) with effective results in increasing understanding of the concepts of mubadalah for prospective bridal couples, and (3) broad-scale trial with effective results increases understanding of the concept of mubadalah for prospective bridal couples. The result of this research is that the formulation of mubadalah marriage guidance is found to be effective in increasing the understanding of the mubadalah concept in the prospective bride and groom, preventing divorce and forming a good (sakinah) family. The results of the limited trial and the effective broad-scale trial were both effective, as seen from the Wilcoxon statistical test which was declared significant (probability < 0.05).